Structure and RNA Interactions of the Plant MicroRNA Processing-Associated Protein HYL1 - Rasia, Rodolfo Maximiliano (2010)
HYL1 is a double-stranded RNA binding protein involved in microRNA processing in plants. HYL1 enhances the efficiency and precision of the RNase III protein DCL1 and participates in microRNA strand selection. In this work, we dissect the contributions of the domains of HYL1 to the binding of RNA targets. We found that the first domain is the main contributor to RNA binding. Mapping of the interaction regions by nuclear magnetic resonance on the structure of HYL1 RNA-binding domains showed that the difference in binding capabilities can be traced to sequence divergence in beta2-beta3 loop. The possible role of each domain is discussed in light of previous experimental data.